Skeletal maturation analysis by morphological evaluation of the cervical vertebrae - Santos, Eduardo Cesar Almada [UNESP]; Bertoz, Francisco Antônio [UNESP]; Arantes, Flávia de Moraes [UNESP]; Reis, Patrícia Maria Pizzo [UNESP]; Bertoz, André Pinheiro de Magalhães [UNESP] (My University, 2006)
The determination of skeletal maturation by morphological evaluation of the cervical vertebrae was evaluated in a 100 cephalograms. The analysis showed that this method was reproducible for assessing the individual's growth curve.
Keywords: adolescent; age determination; axis; cephalometry; cervical spine; child; feasibility study; female; growth; histology; human; male; methodology; observer variation; physiology; reproducibility; Adolescent; Age Determination by Skeleton; Axis; Cephalometry; Cervical Vertebrae; Child; Feasibility Studies; Female; Growth; Humans; Male; Observer Variation; Reproducibility of Results